Preservice Science Teachers’ Demonstration of Critical Thinking Dimensions in Addressing the Socio-scientific Issue of Implementing an Artificial Moon for Street Illumination. - Franco-Mariscal, Antonio Joaquín; Hierrezuelo-Osorio, José Manuel; Cano-Iglesias, María José; Blanco-López, Ángel (Springer Nature, 2024)
Developing critical thinking skills in students is currently a priority objective in both general and science education. Critical thinking is part of non-university and university curricula and teacher training and is promoted by various international organisations. Despite its importance, the development of critical thinking is a challenge for teachers in science education because, among other reasons, there has yet to be a widely accepted model for how to address it successfully in the classroom. The first is that critical thinking is a complex construct involving cognitive factors, skills, and dispositions. Another obstacle is the lack of consensus in science education about the dimensions that comprise it. Furthermore, the nature of the context in which critical thinking is intended to be developed plays an important role in promoting some dimensions or others. However, despite these limitations, there is agreement on the importance of promoting critical thinking for action, both within the curricular framework and in educational research. Recent literature has presented different theoretical approaches to the development of critical thinking in science education, focusing on the use of socio-scientific issues. Although these developments are necessary, it is important to have these theoretical approaches and examples of experiences that show science teachers their designs and how to adapt these integrated approaches to critical thinking to the reality of the classroom, as they are not yet widespread. Analysing these experiences will help teachers identify the dimensions of critical thinking in the activities they propose, integrate them, and provide them with references for new designs. The choice of the problem to be addressed is also important. Energy is a case in point as a key concept in science curricula. Its teaching is still primarily conceptual, although it is increasingly necessary to address it as a socio-scientific issue, given that it is a complex and global challenge that requires mechanisms of action to be carried out both globally and individually. Therefore, this chapter proposes a design for integrating critical thinking into socio-scientific issues and analysing its potential. This aspect needs to be explored in science education, as exemplified in a current case related to energy use.
https://www.springernature.com/gp/open-science/policies/book-policies
Keywords: Ciencia - Aspectos sociales; Pensamiento crítico; Lógica; Toma de decisiones; Critical thinking; Socioscientific issues; Argumentation; Decision-making; Energy